Near interface ionic transport in oxygen vacancy stabilized cubic zirconium oxide thin films - Raza, Mohsin; Sanna, Simone; Dos Santos Gómez, Lucia; Gautron, Eric; El Mel, Abdel Aziz; Pryds, Nini; Snyders, Rony; Konstantinidis, Stéphanos; Esposito, Vincenzo (Physical chemistry chemical physics : PCCP, 2018)
The cubic phase of pure zirconia (ZrO ) is stabilized in dense thin films through a controlled introduction of oxygen vacancies (O defects) by cold-plasma-based sputtering deposition. Here, we show that the cubic crystals present at the film/substrate interface near-region exhibit fast ionic transport, which is superior to what is obtained with similar yttrium-stabilized cubic zirconia thin films.